Beneficial effects of American ginseng (Panax quinquefolius L.) extract residue as a feed additive on production, health status, and gastrointestinal bacteria in sika deer (Cervus nippon) - Wu, Yan; Zhao, Shuting; Zheng, Peihe; Liu, Hanlu; Qu, Zhengyi; Hou, Wei; Yuan, Weitao; Feng, Tao; Zhan, Xiaofeng; Shen, Jinlong; Wang, Kaiying (Frontiers in Microbiology, 2024)
American ginseng residue is an industrial by-product of ginseng saponin extraction, including polysaccharides and amino acids; however, it is often discarded into the natural environment, representing a waste of resources as well as an environmental issue. In this study, we examined the effects of adding American ginseng residue to the basal diet of sika deer. Twelve antler-bearing male sika deer were assigned randomly to groups fed a diet supplemented with 0% (CON), 1% (LGR), and 3% (HGR) American ginseng residue, respectively, (n = 4 per group) for 5 weeks. Supplementation with 3% American ginseng residue significantly increased antler production and feed utilization efficiency in antler-bearing sika deer (p < 0.05). There were no significant differences in serum biochemical indexes among the three groups, but serum immunoglobulin A and glutathione peroxidase levels were significantly increased in the LGR and HGR groups (p < 0.05). Supplementation with American ginseng residue affected rumen fermentation in sika deer, significantly increasing the rumen contents of acetic acid, propionic acid, and total volatile fatty acids, and decreasing rumen fluid pH (p < 0.05), but had no significant effect on microbial protein or ammoniacal nitrogen content. American ginseng residue also affected the rumen bacterial composition, with significant up-regulation of Bacteroidota abundance in the HGR group, significant increases in Fibrobacterota and Fibrobacter abundance in the LGR group, and a significant decrease in Oscillospiraceae_UCG-005. Supplementation with ginseng residue had no significant effect on volatile fatty acids in the feces of sika deer, but did affect the composition of fecal bacteria, with significant decreases in Desulfobacterota and Rikenellaceae_RC9_gut_group in the HGR group, and a significant increase in Ruminococcus in the LGR group (p < 0.05). In addition, the abundance of Paeniclostridium in the feces decreased linearly with increasing concentration of ginseng residue, with a significant difference among the groups (p < 0.05). This study comprehensively evaluated the effects of American ginseng residue as a potential feed additive on the production performance and gastrointestinal bacterial community in antler-bearing sika deer. The results indicated that ginseng residue was a suitable feed additive for improving production performance and health in sika deer.